In vitro synergy of echinocandins with triazoles against fluconazole-resistant Candida parapsilosis complex isolates. (June 2020) - Ahmadi, Ali; Mahmoudi, Shahram; Rezaie, Sassan; Hashemi, Sayed Jamal; Dannaoui, Eric; Badali, Hamid; Ghaffari, Mansoureh; Aala, Farzad; Izadi, Alireza; Maleki, Aida; Meis, Jacques F.; Khodavaisy, Sadegh
Highlights: The distribution of 15 fluconazole-resistant clinical isolates of Candida parapsilosis complex were as follows: Candida parapsilosis sensu stricto (n = 7), C. orthopsilosis (n = 5) and C. metapsilosis (n = 3). In vitro combinations of fluconazole with anidulafungin (fractional inhibitory concentration index, FICI 0.07–0.37), fluconazole with micafungin (FICI 0.25–0.5), itraconazole with anidulafungin (FICI 0.15–0.37) and itraconazole with micafungin (FICI 0.09–0.37) were synergistic. The combination of fluconazole and itraconazole with either anidulafungin or micafungin demonstrated synergistic interactions against C. parapsilosis species complex, especially against isolates with elevated MIC values. Abstract: Introduction: Candida parapsilosis ( C. parapsilosis ) is a common non- albicans Candida species ranked as the second common cause of bloodstream infections. Azole resistance and elevated echinocandin MICs have been reported for these fungi. This study was conducted to determine the interactions between azoles and echinocandins against C. parapsilosis species complex. Materials and methods: Fifteen fluconazole-resistant clinical isolates of C. parapsilosis complex were included: C. parapsilosis sensu stricto (n = 7), C. orthopsilosis (n = 5) and C. metapsilosis (n = 3). The activity of azoles (fluconazole, itraconazole) and echinocandins (anidulafungin, micafungin) alone and in combination was determined using checkerboard broth microdilution. The results were determined based on the fractional inhibitory concentration index (FICI). Results: In vitro combination of fluconazole with anidulafungin was found to be synergistic (FICI 0.07–0.37) and decreased the MIC range from 4–64 μg/mL to 0.5–16 μg/mL for fluconazole and from 2–8 μg/mL to 0.125–1 μg/mL for anidulafungin. Similarly, interactions of fluconazole with micafungin (FICI 0.25–0.5), itraconazole with anidulafungin (FICI 0.15–0.37) and itraconazole with micafungin (FICI 0.09–0.37) were synergistic. Conclusion: The combination of fluconazole and itraconazole with either anidulafungin or micafungin demonstrated synergistic interactions against C. parapsilosis species complex, especially against isolates with elevated MIC values. However, the use of these combinations in clinical practice and the clinical relevance of in vitro combination results remain unclear.